Praktikalitas dan Efektivitas Penggunaan E-Modul Fisika SMA Berbasis Guided Inquiry Terintegrasi Etnosains untuk Meningkatkan Berpikir Kritis Peserta Didik - Rudi Kurniawan; Syafriani Syafriani (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Starting from the lack of students' ability to analyze problems in learning. Given the demands of the times and the Covid-19 pandemic. The teaching materials needed are in the form of electronic modules based on guided inquiry learning models and integrated with ethnoscience, to improve students' critical thinking skills. This e-module supports an independent learning process that can guide students to carry out investigations independently of problems that can be in the form of cultural and customary elements around students, to improve students' critical thinking skills. This research was conducted using the ADDIE development model, to measure the practicality level of the electronic module using a Likert scale. Measurement of the effectiveness of the aspects of knowledge, skills, and attitudes was carried out using the t-test and the Man Whitney U test. The results were obtained from the development of guided inquiry-based e-modules integrated with ethnoscience to improve practical and effective critical thinking skills.